Compound Danshen dripping pills prevent early diabetic retinopathy: roles of vascular protection and neuroprotection - Xu, Xiaoyu; Wang, Mengchen; Zhang, Shuxia; Wang, Jing; Li, Xinxin; Ma, Xiaohui; Luo, Yun; Sun, Xiaobo (Frontiers in Pharmacology, 2024)
Diabetic retinopathy (DR) represents a major cause of adult blindness, and early discovery has led to significant increase in the number of patients with DR. The drugs currently used for treatment, such as ranibizumab, mainly focus on the middle and late periods of DR, and thus do not meet the clinical need. Here, the potential mechanisms by which compound Danshen Dripping Pills (CDDP) might protect against early DR were investigated. Db/db mice were used to establish a DR model. The initial weights and HbA1c levels of the mice were monitored, and retinal pathology was assessed by hematoxylin-eosin (HE) staining. The vascular permeability of the retina and thickness of each retinal layer were measured, and electroretinogram were performed together with fundus fluorescein angiography and optical coherence tomography. The levels of inflammatory factors were examined in retinal tissue, as well as those of intercellular adhesion molecule 1 (ICAM-1), IL-6, and monocyte chemoattractant protein 1 (MCP-1) in the serum using ELISA. Immunohistochemistry was used to evaluate levels of vascular endothelial growth factor (VEGF), B-cell lymphoma 2 (Bcl-2), and Bclassociated X protein (Bax). Retinal cell injury and apoptosis were examined by TdT-mediated dUTP Nick-End Labeling (TUNEL) assays. The data showed that CDDP significantly improved cellular disarrangement. Imaging data indicated that CDDP could reduce vascular permeability and the amplitude of oscillatory potentials (OPs), and restore the thickness of the ganglion cell layer. Moreover, CDDP reduced the expression levels of inflammatory factors in both the retina and serum. These findings strongly suggest that CDDP prevents early DR through vascular and neuroprotection.